FAKTOR-FAKTOR PENYEBAB KEHAMILAN RESIKO TINGGI PADA USIA REMAJA DI PMB HERASDIANA KOTA PALEMBANG TAHUN 2024 - Rosdiana, Meta; Khoiriah, Annisa (LPPM STIKes Mitra Adiguna, 2025)
High risk pregnancy is mother and embryo dengerous situation pregnancy. The objective of the study was to find out the factors correlate the high risk pregnancy to adolescence at PMB Herasdiana Palembang Tahun in 2024. An analytical survey method through cross sectional approach was used in this study. The population of this study was all pregnant mothers who visited PMB Herasdiana Palembang in 2024. The non random sampling through accidental sampling technique was used in this study. The total number of the sample was 30 respondents. Based on univariate analysis, it was found that there were 13 (43.3%) mothers at high risk pregnancy 11 (36.7%) mothers at low educational background, and 17 (56.7%) mothers have lack knowledge. Moreover, based on bivariate analysis, it was found that there was a significant correlation between education and high risk pregnancy with p-value = 0.002 ? ? 0.05 and there was a significant correlation between knowledge and high risk pregnancy with p-value = 0.002 ? ? 0.05. Finally, it is hoped that PMB Herasdiana stakeholders could improve the information about high risk pregnancy to adolescence. Keywords— Education, Knowledge, High Risk Pregnancy